2017
DOI: 10.1128/jvi.02488-16
|View full text |Cite
|
Sign up to set email alerts
|

A Cytoplasmic RNA Virus Alters the Function of the Cell Splicing Protein SRSF2

Abstract: To replicate efficiently, viruses must create favorable cell conditions and overcome cell antiviral responses. We previously reported that the reovirus protein 2 from strain T1L, but not strain T3D, represses one antiviral response: alpha/beta interferon signaling. We report here that T1L, but not T3D, 2 localizes to nuclear speckles, where it forms a complex with the mRNA splicing factor SRSF2 and alters its subnuclear localization. Reovirus replicates in cytoplasmic viral factories, and there is no evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 82 publications
1
47
0
1
Order By: Relevance
“…The localisation of the protein in multiple cellular compartments and the presence of predicted DNA binding and activator domains indicate pleiotropic functions of 3a that most probably involve the reprogramming of the transcriptional regulation of the infected cells. Viral proteins with similar multiple (cytosolic and nuclear) localisations were identified in several different viruses (e. g. 7ap of PRRSV, X protein of hepatitis B virus, μ2 of reovirus T1L (Mbisa et al, 2000;Henkler et al, 2001;Ma et al, 2011;Olasz et al, 2016Olasz et al, , 2017aRivera-Serrano et al, 2017) with proven nucleic acid binding and/or transcription regulating capabilities. Acta Veterinaria Hungarica 66, 2018 Protein 3b was found to localise in the mitochondrion and the nucleolus (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The localisation of the protein in multiple cellular compartments and the presence of predicted DNA binding and activator domains indicate pleiotropic functions of 3a that most probably involve the reprogramming of the transcriptional regulation of the infected cells. Viral proteins with similar multiple (cytosolic and nuclear) localisations were identified in several different viruses (e. g. 7ap of PRRSV, X protein of hepatitis B virus, μ2 of reovirus T1L (Mbisa et al, 2000;Henkler et al, 2001;Ma et al, 2011;Olasz et al, 2016Olasz et al, , 2017aRivera-Serrano et al, 2017) with proven nucleic acid binding and/or transcription regulating capabilities. Acta Veterinaria Hungarica 66, 2018 Protein 3b was found to localise in the mitochondrion and the nucleolus (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Some viruses with RNA genomes that replicate in the nucleus of infected cells have been shown to manipulate other types of nuclear bodies to enhance viral replication. There is now a growing appreciation for the manipulation of nuclear processes by cytoplasmically replicating viruses (3740). Here we report that in addition to its known cytoplasmic localization, the rotavirus IFN antagonist protein NSP1 is also found in the nucleus of infected cells.…”
Section: Discussionmentioning
confidence: 99%
“…Other cytoplasmically replicating dsRNA viruses have also been shown to express proteins that localize to the nucleus. The reovirus μ2 protein, which interferes with the type I IFN response in a strain-specific manner (58, 59), has been shown to localize to nuclear speckles and alter host cell splicing (40). Orbiviruses including bluetongue virus (BTV) and African horse sickness virus express a nonstructural protein NS4 that has been shown to localize to the cytoplasm and nucleus of infected cells (6062).…”
Section: Discussionmentioning
confidence: 99%
“…The main strength of this study is that both AS‐PCR and mass spectrometry were used to validate the results, giving additional weight to the findings. In contrast, a later study by another group showed a limited effect of the T3D virus compared to the reovirus serotype 1‐Lang strain (T1L) (Rivera‐Serrano et al, ). This apparent discrepancy is likely attributable to variations in the actual amino acid sequences of the T3D strain used in different laboratories (Sandekian & Lemay, ).…”
Section: Contribution Of High‐throughput Approachesmentioning
confidence: 93%